Clinicopathological features of Complicated Colorectal Cancers: A 10 Year Retrospective Study in Egypt - Torky, Radwan Abdelsabour; RM, Farghaly; Hussein, Ahmed M.; Abdeltawab, Asmaa A. (Asian Pacific Journal of Cancer Care, 2025)
Purpose: The prognosis for emergency surgery for colorectal cancers (CRCs) and metastatic tumors was reported to be extremely poor. Our objective is to ascertain the clinical characteristics of patients who have been diagnosed with complications and metastases at two tertiary centers in Egypt. Methods: a comparative retrospective study between complicated and non-complicated CRCs conducted in two tertiary centers in Egypt over 10 years. Results: a total of 320 patients underwent surgery for CRC, of which 25% underwent emergency surgery (80 cases) and 240 (75%) patients underwent an elective one. There was a higher rate of complicated colon and non-complicated rectal cancer (P=0.009). There was a significantly higher rate of positive L.Ns, positive LVI and PNI (P = 0.001), (P <0.001) and (P <0.001) respectively in complicated group. In multivariate analysis, only the tumor site (right colon P= 0.010, left colon P= 0.022) as well as the LVI (P= 0.038) remained the most important predicting factors for complication. There was a significantly higher rate of OS in patients with T1 and T2 (P= 0.002), in patients with grade I and II (P= 0.005), node-negative and non-metastatic disease with (P=<0.001) and (P= <0.001) respectively. Conclusion: Right and left colon cancers, along with positive LVI, are regarded as risk factors for emergency complications and metastases meanwhile advanced stages, unfavorable grades, and node-positive tumors, are associated with a poor prognosis in both groups.